Analisis Antarmuka Pengguna pada Sistem Informasi Desa (OpenSID) Gampong Keubang Kabupaten Pidie dalam Perspektif Interaksi Manusia dan Komputer - Rinov Ananda Ramadana Ananda Ramadana; Junaidi Salat; Qadri; Fhandi Hikmal; Cut Nursilul (TECHSI - Jurnal Teknik Informatika, 2025)
This study aims to analyze the user interface of the Village Information System (OpenSID) in Gampong Keubang, Pidie Regency, based on Human-Computer Interaction (HCI) principles. The research uses direct observation and documentation of system interfaces such as the dashboard, village service menus, population data, and administrative features. The analysis focuses on usability aspects, including ease of use, design consistency, text readability, navigation, and user needs compliance. The findings indicate several issues, such as unstructured layout, icons without text labels, low color contrast, and important information that is not immediately visible. However, the system has sufficiently supported village officials in managing data digitally. This study is expected to provide recommendations for improving the OpenSID interface design to be more user-friendly and in line with user needs.